Blockchain for Smart Cities: Waste Management with Smart Contracts - Canpolat, Nida; Yetiş, Hasan; Karaköse, Mehmet (Institution of Engineering and Technology, 2024)
The term Blockchain is a very popular and new technology today. Blockchain first emerged to verify file timestamp information and later became very popular with virtual currencies called Bitcoin. Blockchain technology has become so popular because it provides security, is not connected to a central system, its information is unchangeable, has a wide range of usage and offers a transparent structure. This technology is frequently used actively in many areas such as financial structures, healthcare services, buying and selling transactions, education, real estate transactions, smart cities and voting systems. One of the structures actively used on Blockchain is the smart contract structure. The smart contract which enables the contracts determined by the users to run automatically, is executed on a Blockchain network and automatically executes the desired transactions in a secure manner. Smart contracts can be used integrated into many areas and Blockchain structures. With the developing technology smart contract and Blockchain technology have begun to be used frequently in smart city projects. In particular they can be used in a variety of processes such as energy management, logistics, waste management, transportation, real estate, healthcare, utilities and administration. In this study a waste management example based on smart contracts was implemented using Blockchain technology. Because waste management is very important for smart cities. Waste management has an important role in many issues such as health, hygiene, environmental efficiency and resource management. For this purpose a smart contract-based waste management example has been developed. The developed sample contract includes the recycling process based on the collection of waste. With this contract, the amount of recycled waste is controlled and the user is rewarded. A recycling project that can be used in smart city projects is aimed to make the process automatic and safer by combining it with smart contract and Blockchain technology. © The Institution of Engineering & Technology 2024.
8th IET Smart Cities Symposium, SCS 2024 -- 1 December 2024 through 3 December 2024 -- Hybrid, Sakhir -- 208334
Keywords: Blockchain; Remix IDE; Smart City; Smart Contracts; Waste Management